2013
DOI: 10.5380/rf.v43i1.26021
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Capacidade De Trabalho E Do Perfil De Trabalhadores Em Serrarias No Município De Eunápolis, Ba

Abstract: ResumoA pesquisa foi desenvolvida no município de Eunápolis, Bahia, com o objetivo de determinar o perfil dos trabalhadores de serrarias, bem como a sua capacidade de trabalho. O perfil dos trabalhadores foi avaliado por meio de questionário. Para avaliar a capacidade de trabalho, utilizou-se uma versão adaptada para uso no Brasil do Índice de Capacidade de Trabalho (ICT), um questionário que permite avaliar a capacidade para o trabalho a partir da percepção do próprio trabalhador. A população analisada englob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
2
1
1
Order By: Relevance
“…This proportion is similar to the reduced work ability of 11.3 % observed by Fischer and Martinez [ 24 ] among nursing professionals at a hospital in São Paulo, Brazil. By contrast, the percentage of workers with reduced work ability determined in the present study is lower than that reported in other Brazilian studies: 20.4 % for workers in hospital housekeeping services [ 25 ]; 34.5 % for workers in sawmills [ 26 ]; 35.3 and 46 % for municipal school teachers [ 27 , 28 ]; and 43.3 % in nurses [ 29 ].…”
Section: Discussioncontrasting
confidence: 93%
“…This proportion is similar to the reduced work ability of 11.3 % observed by Fischer and Martinez [ 24 ] among nursing professionals at a hospital in São Paulo, Brazil. By contrast, the percentage of workers with reduced work ability determined in the present study is lower than that reported in other Brazilian studies: 20.4 % for workers in hospital housekeeping services [ 25 ]; 34.5 % for workers in sawmills [ 26 ]; 35.3 and 46 % for municipal school teachers [ 27 , 28 ]; and 43.3 % in nurses [ 29 ].…”
Section: Discussioncontrasting
confidence: 93%
“…The WCI questionnaire presents 7 items, with scores that vary from 7 to 49 points, and is calculated through the sum of each one of the seven items, where it is classified into four different categories of work capacity. Based on the final score, the results can reach scores of 7 to 49 points, with 7 to 27 being classified as a low work capacity, from 28 to 36 as moderate, from 37 to 43, as good, and 44 to 49 as excellent, according to Tuomi and Ilmarinen (1997) (Cerqueira and Freitas 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In general, the main risks related to ergonomics in the workplace are due to organizational aspects, such as the high production rate, inadequate postures of the worker and excessive overtime [2]. All these aspects make the worker adapt quickly to situations imposed by the workplace, supporting uncomfortable and inadequate positions throughout the work period [3].…”
Section: Introductionmentioning
confidence: 99%